SUSTAINABLE E-GOVERMENT IN PUBLIC SERVICE INNOVATION (Study on the Implementation of All In One Indramayu Information Technology in Indramayu Regency) - Ibrahim Ibrahim; Samugyo Ibnu Redjo; Neneng Yani Yuningsih (Universitas Pancasakti Tegal, 2023)
During the Covid-19 pandemic, technology played an important role in keeping community activities running as they should. The practice of using information technology for the community is directed at increasing the reliability of community service technology, the effectiveness and efficiency of receiving services by the community. This study uses descriptive qualitative, where in data collection using secondary data in the form of documentation at the research location. The data analysis technique is a descriptive analysis technique, in which the analysis is carried out to be able to explain the Application of All In One Information Technology in Improving Public Services in Indramayu Regency. The results of the research show that the application of All In One Information Technology in Indramayu Regency. There are several inhibiting factors both in the socialization and implementation of these applications including internal and external factors, internal factors are inhibiting factors from within, namely the lack of IT experts as system operational controllers and not yet maximal training specifically in the field of IT, limited budgets, lack of supporting facilities such as Inadequate buildings and also the absence of special IT media buildings and tools.